Speaking tasks for the assessment of English: the use of linkers - Marcos Peñate Cabrera (Revista de Lingüística y Lenguas Aplicadas)
Although assessment experts have been researching the relationship between the different types of tasks and their level of difficulty, this process of analysis should be pursued further in order to acquire a more accurate vision of the variables involved. In this article we study the three types of tasks most frequently used in the different models of oral exams (one-to-one interview based on a photo, one-to-one interview based on a comic strip and a dialogue in pairs). In order to carry out this study we assessed 244 pupils from the second year of Bachillerato belonging to nine different schools and having an A2 level of English. When contrasting the 3 types of tasks, our aim was to analyse the amount and complexity of the oral production, namely the use of linkers, by means of statistical tests of homogeneity and specificity.